PENGEMBANGAN KARIER, MOTIVASI KERJA, DAN KINERJA DOSEN DI STIKES KARYA HUSADA KEDIRI - Triana, Neny; Puspita, Sylvie (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background: The development organization is an essential part of the education system in universities. Human Resources lecturer capabilities as one indicator of the quality of the education agency that fi t the criteria of the Directorate General of Higher Education. Lecturers must be professional in the line of duty Tri Dharma College (Directorate General of Higher Education, 2010).Objective: To describe the career development, motivation, and performance STIKES Karya Husada Lecturer in Kediri.Methods: Posivistik qualitative research, action research, sampling techniques: purposive sampling on informants who know most about work STIKES Husada Kediri, then searching for information on informants to be valid and complete.Data collection: observation, interviews and documentation, the data were analyzed: domain analysis.Results: Results of the study: 1) Development of career planing: further studies lecturer, fi ling functional position Lecturer, training manners and Applied Approach, Career Management of: mapping of further studies lecturer, fi ling functional, training implementation manners and Applied Approaach, 2) Motivation Internal: Changing image principal tasks and functions Lecturer, work motivation is external: change the payroll system, 3) Performance Lecturer: Competence Pedagogic: understanding the character of lecturers and training implementation Competency Based Curriculum (CBC), Professional Competence: Adjustment of the activities of Tri Dharma College, Competence Personality: training personality. build teamwork in outbound activities, Social Competence: Open yourself to accept criticism and suggestions, improve internal relations and ektern institution.Conclussion: Conclusions and suggestions: 1) Development of a career, should be followed up with a follow-up, always motivate lecturers to continue on to graduate in order to improve career Lecturer. 2) Work Motivation Lecturer: internal work motivation maintained Lecturer to support external motivation to work, so that the Foundation was pleased to see his teachers eager to work with the standard equation payroll system based on Civil Servants (PNS). 3) Performance Lecturer in the application of pedagogical competence, professional competence, social competence and personal competence should be maintained.Keywords: Development, Career, Work Motivation, Performance Lecturer